Optimalisasi program usaha kesehatan sekolah untuk kesehatan mental siswa - Nurochim Nurochim (Indonesian Institute for Counseling, Education and Therapy (IICET), 2020)
Health and education are important factors in the sustainability of a country. Health is not only physical health but also mental health is very important to maintain its quality. Student mental health is a condition without mental disorders, health because of stress, so it can play a role in life. The method used in this article is literature review. This study seeks to uncover how school health efforts are as effective programs to promote school-based mental health. Kajin results show that a planned and measured health business program can be a means of promoting school-based mental health. The UKS program is health education, health services, and fostering a healthy school environment. An effective and efficient UKS program is supported by strong leadership and cooperation across related sectors. This is supported by three forces namely, institutions, cognitive frames, and social networks.